Climate Change Gender Action Plan of the Federal Democratic Republic of Ethiopia - Tesfaye, Abonesh; Mohammed, Abas; Andoshe, Mohammed; Legesse, Ketema; Zewdie, Yihenew; Salih, Bashir; Mulatu, Ayalneh; Ambaw, Gebermedihin; Makonnen, Brook T.; Huyer, Sophia; Aregu, Lemlem; Tesfaye, Lidya; et al. (Government of Ethiopia, 2024)
Ethiopia is highly vulnerable to climate change due to its dependency on rain-fed agriculture and natural resources and its low adaptive capacity to absorb climate change-induced shocks. Climate change impacts men and women differently, largely due to their gender-differentiated relative powers, roles and responsibilities at the household and community levels. Ethiopian women normally have lower access to resources, information, participation, and decision-making processes compared to men due to persistent gender inequality. Their limited access to productive resources combined with their disadvantaged societal position increases their vulnerability to climate change-induced distress. Recognizing these gender-specific impacts of climate change, the Government of Ethiopia is committed to addressing the climate crisis by being gender-responsive in its policies, strategies and programs. The government draws on policy and planning advancements, including sectoral climate-resilient strategy, the National Adaptation Plan (NAP 2017) and the NAP Implementation Roadmap (2019) and specifies 40 adaptation interventions. The country has also demonstrated its clear commitment by submitting its updated nationally determined contribution (NDC) and pursuing practical action through its green legacy initiative. The updated NDC provides a suite of sectoral priority interventions that guide sectors, development partners, development financing institutions, the private sector, and other stakeholders in designing and implementing the enhanced NDC’s activities. In addition to the NDC, the newly launched 10 YDP and Ethiopia’s 2050 Low Emission Development Strategy are clear indicators of Ethiopia’s commitment to adaptation and mitigation measures. The Government reflects gender priorities in its promises for climate action by making Ethiopia’s sectoral strategies, plans and actions gender sensitive. This Climate Change Gender Action Plan (CCGAP) document is prepared to provide space for properly integrating gender issues into Ethiopia’s climate action. The objective of this CCGAP is to ensure that Ethiopia’s climate change processes mainstream gender considerations to guarantee that women and men can have access to, participate in, and benefit equally from climate change initiatives. This document would guide regional and local governments in mainstreaming gender concerns to address climate change challenges in Ethiopia. The action plan is a living document that is subject to regular updates, and it involves a collaborative effort among the different priority sectors, the MoWSA and the MoPD, to ensure that gender is fully incorporated in the national initiatives and policies on the topic of climate change.